Meta-Analysis of Cytochrome P-450 2C9 Polymorphism and Colorectal Cancer Risk - Liang, Shuo; Hu, Jingsong; Cao, Weijun; Cai, Sanjun (PLOS ONE, 2012)
Background CYP2C9 encodes a member of the cytochrome P450 superfamily of enzymes which play a central role in activating and detoxifying many carcinogens and endogenous compounds thought to be involved in the development of colorectal cancer (CRC). In the past decade, the relationship between CYP2C9 common polymorphisms (R144C and I359L) and CRC has been reported in various ethnic groups; however, these studies have yielded contradictory results. To investigate this inconsistency, we performed this meta-analysis. Methods Databases including Pubmed, EMBASE, Web of Science and China National Knowledge Infrastructure (CNKI) were searched to find relevant studies. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the strength of association. Results A total of 13 articles involving 9,463 cases and 11,416 controls were included. Overall, the summary odds ratio of CRC was 0.98 (95% CI: 0.89−1.06) and 0.99 (95% CI: 0.87−1.14) for CYP2C9 144C and 359L alleles, respectively. No significant results were observed using dominant or recessive genetic model for these polymorphisms. In the stratified analyses according to ethnicity and sex, no evidence of any gene-disease association was obtained. Conclusions This meta-analysis suggests that the CYP2C9 may not be associated with colorectal cancer development.